Relationship between quality attributes of backslopped fermented gari and the sensory and instrumental texture profile of the cooked dough (eba) - Awoyale, W.; Oyedele, H.A.; Adenitan, A.A.; Adesokan, Michael; Alamu, Emmanuel Oladeji; Maziya-Dixon, Busie (Hindawi Limited, 2022)
Knowledge is scarce on the drivers of textural characteristics of cooked dough prepared from gari (eba). To address this need, quality attributes of backslopped fermented gari (BFG) were correlated with the sensory texture profile analysis (STPA) and instrumental texture profile analysis (ITPA) of the eba produced from six cassava varieties. The results showed that a significant and negative correlation exists between the STPA mouldability of the eba and the sugar (p < .05, r = −0.83) and amylose (p < .05, r = −0.86) contents of the BFG. The STPA stretchability of the eba had a significant negative correlation with the bulk density (p < .05, r = −0.83) and a significant positive correlation with the setback viscosity (p < .01, r = 0.92) of the BFG. A significant and negative correlation exists between the STPA stickiness of the eba and the amylose (p < .05, r = −0.84) contents of the BFG. The ITPA adhesiveness of the eba was significant and negatively correlated with the solubility index (p < .05, r = −0.89) and the ash content (p < .05, r = −0.87) of the BFG. The correlation between the ITPA stretchability of the eba and the peak (p < .05, r = 0.83) and breakdown (p < .05, r = 0.88) viscosities of the BFG was significant and positive, while a significant negative correlation (p < .05, r = −0.83) exist between the ITPA stretchability of the eba and the starch content of the BFG. The information provided in this study may assist the breeders in developing varieties with good textural attributes for eba.